The Effect of Oxytocin Massage on Breast Milk Production and Uterine Recovery in Postpartum Mothers - Abimulyani, Yumi; Sawedi, Ismawanti (Oshada, 2025)
Breast milk (ASI) is the ideal nutrition for newborns because it contains complete nutrition, antibodies, and irreplaceable protective factors. However, many postpartum mothers experience delayed milk production due to physiological and psychological barriers, which can reduce the success of exclusive breastfeeding. One effective non-pharmacological intervention is oxytocin massage, a light massage technique along the spine and ribs to stimulate the release of the hormone oxytocin. This mechanism supports the milk ejection reflex (let-down reflex) through contraction of breast myoepithelial cells and accelerates the release of colostrum. In addition to its benefits for lactation, oxytocin also plays a role in accelerating uterine involution, thereby reducing the risk of postpartum hemorrhage. The psychological effects of relaxation and reduced anxiety contribute to successful breastfeeding and increase maternal self-confidence. Despite physiological and clinical evidence, the implementation of oxytocin massage in the field remains limited due to lack of training, limited socialization, and suboptimal integration into postpartum care standards. This study used a literature review method to analyze the mechanisms, benefits, and challenges of implementing oxytocin massage. The study results confirm that oxytocin massage is a simple, safe, and effective intervention that has the potential to increase the success of exclusive breastfeeding while accelerating maternal recovery.